MODEL PERUBAHAN TUTUPAN LAHAN BERBASIS CA-MARKOV: STUDI KASUS KECAMATAN TERNATE UTARA, KOTA TERNATE - Panji Nurul Achmadi; Muhammad Dimyati; Masita Dwi Mandini Manesa; Heinrich Rakuasa (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
North Ternate Sub-district is located in the center of Ternate City, making it a sub-district that has an increasing population every year. The increase in population certainly affects the increase in built-up land, which certainly affects environmental damage, climate change and other socio-economic problems. This study aims to predict land cover change in North Ternate Sub-district in 2003, 2013, 2023 and 2032 based on CA-Markov. This research used CA-Markov method to predict land cover in 2023. The results showed that in 2003, 2013, 2023 and 2032, built-up land annually experienced an increase in area, this is certainly influenced by the increase in population, and the need for land for settlement is getting higher every year. Agricultural land, non-agricultural land and open land continue to decrease in the area due to the conversion of these types of land cover to built-up land. The results of this prediction are very useful for the government in making policies related to sustainable spatial planning in the future.